Demonstrasi dan Pengembangan Produk Olahan Nugget dan Fishball dari Ikan Patin sebagai Upaya Pemanfaatan Protein Berkualitas Tinggi di Desa Sungai Bakau - Zukhra, Ririn Muthia; Azra, Azzumardi; Irmaningsih, Yogi; Saputra, Angga Reza; Indriani, Nia; Ningrum, Nurmalisadikin Setia; Lestari, Lestari; Sari, Nurfiya; Nurfalah, Saputri; Syahputra, Fahmi; Alfitra, Nur Fadia (Nanggroe: Jurnal Pengabdian Cendikia, 2024)
The project aims to demonstrate and develop processed nugget and fishball products from Patin fish, leveraging the high-quality protein content of this locally abundant species. Patin fish, known for its rich nutritional value, serves as a primary resource for creating innovative and marketable food products. The project is conducted in Sungai Bakau Village, where community members are introduced to the benefits of utilizing Patin fish in daily diets. Through a series of workshops, participants learn various processing techniques, including proper fish handling, preparation, seasoning, and forming the fish into nuggets and fishballs. These training sessions emphasize hygienic production methods and food safety to ensure the creation of high-standard products suitable for local and regional markets. The initiative also aims to increase the economic potential of Patin fish farming in the area by adding value to the fish through these processed products. By creating marketable food items, the project helps to diversify income sources for local fishermen and entrepreneurs. Furthermore, the project underscores the importance of high-protein foods in promoting public health, particularly in rural communities. The resulting products are expected to appeal to a wide audience due to their convenience, nutritional benefits, and alignment with local culinary preferences. Ultimately, the project not only supports sustainable fisheries management but also contributes to food security and economic resilience in Sungai Bakau Village.